If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(-2a) = 3a(x + -2a) Remove parenthesis around (-2a) x * -2a = 3a(x + -2a) Reorder the terms for easier multiplication: -2x * a = 3a(x + -2a) Multiply x * a -2ax = 3a(x + -2a) Reorder the terms: -2ax = 3a(-2a + x) -2ax = (-2a * 3a + x * 3a) Reorder the terms: -2ax = (3ax + -6a2) -2ax = (3ax + -6a2) Solving -2ax = 3ax + -6a2 Solving for variable 'a'. Combine like terms: -2ax + -3ax = -5ax -5ax + 6a2 = 3ax + -6a2 + -3ax + 6a2 Reorder the terms: -5ax + 6a2 = 3ax + -3ax + -6a2 + 6a2 Combine like terms: 3ax + -3ax = 0 -5ax + 6a2 = 0 + -6a2 + 6a2 -5ax + 6a2 = -6a2 + 6a2 Combine like terms: -6a2 + 6a2 = 0 -5ax + 6a2 = 0 Factor out the Greatest Common Factor (GCF), 'a'. a(-5x + 6a) = 0Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(-5x + 6a)' equal to zero and attempt to solve: Simplifying -5x + 6a = 0 Reorder the terms: 6a + -5x = 0 Solving 6a + -5x = 0 Move all terms containing a to the left, all other terms to the right. Add '5x' to each side of the equation. 6a + -5x + 5x = 0 + 5x Combine like terms: -5x + 5x = 0 6a + 0 = 0 + 5x 6a = 0 + 5x Remove the zero: 6a = 5x Divide each side by '6'. a = 0.8333333333x Simplifying a = 0.8333333333xSolution
a = {0, 0.8333333333x}
| T-7b=3 | | 343/5832 | | X+12=y | | M+9=n | | t^2+2t-5=0 | | 2xy+8x-3y-4=0 | | -8s^2-9s-2=0 | | (y^2)/(2y^2) | | y^2/2y^2 | | 6+4x-2=6x-3-8 | | -3d^2+9d-2=0 | | 17r-8m+2r= | | X+24+4x=-44-4x-49 | | -23+13y+10n-5y-5n-12= | | x+3-2(x+4)=8x-2 | | (8+z)(5z+7)=0 | | 4/18-4x/3=11/6 | | 2.3(4.2-3.8)=5.8(6.2-3.1q)+10.36 | | 80/(1-0.2) | | x+22=99 | | (2x-y+2)dx+(4x-2y-1)dy=0 | | sin^2(x)=1+2sinx | | 7(-x+4)+16=5x-1(10x-6)-6 | | -3y^2-8y-5=0 | | 9+4f-7z= | | m=4n+11 | | t=-15 | | 2x-21=9x-7 | | Cos^2(x)=2+2sinx | | 16/x=18/27 | | 4-3i/i | | log(4-5x)=log(x+10) |